On Endogenous Risk, the Amplification Effects of Financial Systems and Macro Prudential Policies - Giovanni Majnoni; Andrew Powell (Inter-American Development Bank (IDB), 2011)
The recent global financial crisis has put the spotlight on macro-prudential policies to protect firms and households from problems emanating from the financial sector. This paper proposes an analytical framework that combines exogenous and endogenous risks, the latter seen as stemming from frictions in financial markets. Arguing that endogenous risks may be systemic and costly, the paper employs a database of emerging market corporate bond spreads and finds evidence that endogenous risks are present and have amplified the effects of financial crises. Larger financial systems are found to exacerbate the impact of crises, and weaker financial systems are found to exacerbate particularly the impact of banking crises. The results suggest that policymakers should monitor time-varying systemic risks using both price and quantity signals and take actions in good times to mitigate potential amplifying effects at times of stress.
Keywords: E32; E44; E58; F30; G30; 330